Ergonomic considerations in libraries a study of the librarians' workplace in Intramuros library consortium - Occeña, Kimberly Ann M. (2014)
The addition of computers in industries facilitates tasks quickly and easily. In libraries, tasks are minimized such that the encoding of data entails the production of the cards and the call number labels simultaneously. However, there have been several downsides to the use of technologies especially that of computers in the workplace. This study sought to determine the work place conditions in relation to the use of technology among member-libraries of the Intramuros Library Consortium. A total of 35 librarians and library staff were surveyed for the study. The Occupational Safety and Health Administration (OSHA) and the work of Timoteo (2009) and Bugais (2005) on ergonomics were used as references for the existing workplace furnishing and set-up of the member-libraries.